Arts and Humanities Research Council (AHRC) - Arts & Humanities Research Council (2011)
[Dt.:] AHRC ist das offizielle Forschungsgremium in Großbritannien, das postgraduierte Forschung im Bereich der Geistes- und Kulturwissenschaften unterstüzt und fördert. Ziel ist eine qualifizierte geisteswissenschaftliche Forschung und eine breitere Akzeptanz innerhalb der Gesellschaft. Die Website informiert über die Möglichkeiten der Beantragung von Forschungsprojekten. - [Engl.:] The Arts and Humanities Research Council, UK, supports high-quality and innovative research in the arts and humanities and promote awareness of the importance of arts and humanities research and its role in understanding the society. The AHRC was launched in April 2005 as the successor organisation to the Arts and Humanities Research Board (AHRB). The AHRB, formally launched in 1998, had been established as an interim and transitional body, pending a decision from Government on the recommendation in the Dearing Report of 1997 that an arts and humanities research council be founded.